Coronavirus disease 2019 and the cancellation of face-to-face prostate cancer active surveillance clinic reviews: Does the omission of digital rectal examination alone put patients at risk of missed detection of disease progression?. (March 2022) - Maresca, Gianluca; Akinlua, Akintobi; Wardlaw, Kevin; Macdonald, Graham; Royle, Justine
Objectives: The coronavirus disease 2019 (COVID-19) pandemic has resulted in the cancellation or postponement of face-to-face clinic appointments, meaning patients on active surveillance (AS) for low- or intermediate-risk prostate cancer have been unable to undergo the recommended clinical assessment and digital rectal examination (DRE) during these times. This study aimed to determine whether the omission of DRE during the COVID-19 pandemic has put AS patients at risk by missing early detection of disease progression. Methods: This was a retrospective, regional study looking at the data of 142 men who qualified for placement on the Grampian AS protocol over a six-year span. It paid particular attention to the reasons for progression in those men who moved to active treatment (AT) during this six-year period. Results: The results showed that DRE played no role in triggering the move of these 42 patients onto AT. Nineteen (45%) of these patients moved to AT due to progression on trans-rectal ultrasound biopsy, 10 (24%) due to progression on multi-parametric magnetic resonance imaging, eight (19%) due to a rising prostate-specific antigen and five (12%) due to patient choice. Conclusion: This audit reassures us that those patients who cannot receive a timely DRE during the COVID-19 pandemic are unlikely to be at an increased risk of missing disease progression in our region. Level of evidence: Retrospective cohort study – level 3.